Unsur Tokoh dan Nilai Kehidupan dalam Fabel Indonesia dan Fabel Terjemahan - Kuswara Kuswara (STKIP Sebelas April Sumedang, 2021)
This study examines and compares the character elements and the content of life values in Indonesian and Chinese fables. Chinese fables showed more numbers and types of characters than Indonesian fables. Indonesian fables only showed actors in the form of animals with a total of 18 types of animals. Chinese fables featured four types of actors, namely animals (29 types), humans, inanimate objects, and supernatural beings. The frequency of life values in Chinese fables is much more (65 pieces) than in Indonesian fables (28 pieces), therefore; the forms of life values in Chinese fables were more diverse. The creativity of Indonesian fable writers is lower than that of Chinese fable writers. Indonesian fables still fully refer to the concept that fables feature animal characters and are entertaining.